PECULIARITIES OF FORMATION AND USE OF INFORMATION ABOUT FINANCIAL RESULTS OF ACTIVITY OF BUSINESS ENTITY AS A RESULT OF EFFECTIVE PERFORMANCE - LOPATOVSKYI, VICTOR; KRASUTSKYI, ROSTYSLAV (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Research on financial performance and income taxation in times of economic downturn and crisis is always gaining attention and popularity, because the amount of profit depends on the viability of the enterprise, the level of wages and, accordingly, turnover and skills, and as a result of state budget revenues. different levels.Income tax, in turn, is a regulator of the distribution between the state and enterprises of all forms of ownership of profits, as the main source of innovation and investment activities.The current conditions and the economic situation in Ukraine and in the world as a whole pose new challenges for enterprises to optimize their activities, efficiency in the face of growing competition, the impact of aggressive internal and external factors. No business activity has development prospects without a positive financial result, which lacks the dynamics to grow. Profit has always been the main indicator of business efficiency. That is why the formation and definition of profit has caused and continues to cause so much debate in economics, as evidenced by the great variety of theories on its definition and sources of formation. This area of research attracts a lot of attention during the crisis, as profit is the most desirable source of resource recovery and enterprise development. Therefore, maintaining profitability at a sufficient level is a challenge for managers at all levels and divisions of the enterprise, especially given today's oversaturated and over-competitive environment, where every enterprise is fighting for survival. The authors investigate the peculiarities of the formation and use of information about financial results as an effective indicator of enterprise activity, which is formed according to the system of its accounting and reporting and used by management to make management decisions on profit management.Financial results are a measure of the efficiency of any commercial enterprise, making a profit - the main purpose of doing business. Domestic and foreign scientists have prepared many scientific papers to highlight the peculiarities of the formation and use of information about financial results, but the main problem is that there is no one-size-fits-all solution to optimize financial results and increase profitability.The current economic turmoil shows new weaknesses in the activities of economic entities and policies to increase their profitability, and therefore research and writing scientific papers and practical recommendations on this topic will always be relevant.
Keywords: financial results; accounting; reporting; profit; loss; income; expenses; profit management